ANALISIS HASIL PEMILIHAN GUBERNUR KALIMANTAN TIMUR TAHUN 2018 DI KABUPATEN KUTAI KARTANEGARA EFRI NOVIANTO - Efri - novianto (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2018)
This research is aimed to analyze the result of East Kalimantan governor election in Kutai Kartanegara Regency. This research uses descriptive survey approach. Data collection was done by face-to-face directly using the questionnaire on 28 May until 7 June 2018 in 6 subdistricts namely Tenggarong, Tenggarong Seberang, Sebulu, Loa Kulu, Loa Janan and Kota Bangun with 117 respondents. From the result of the research, it can be concluded that Isran Noor-Hadi Mulyadi and Syaharie Jaang-Awang Ferdian Hidayat who is the son of the region succeeded in maximizing tribal identity, so that they won the majority of voters from their respective tribes. The victory of Isran Noor-Hadi Mulyadi pair is due to the capability of the party machine in the winner, especially the PKS machine which is a representation of Hadi Mulyadi. It is also due to the solidarity of the couple's voters unaffected by money politics. Keywords: Pilgub, Tribal Identity, Party Machine, Solidity of Voters